ECOHUMAN IN NEW MATERIALIST HUMANISM: “ENERGY AND CHANGE” BY CLAYTON CROCKETT (Glocalism: Journal of Culture, Politics and Innovation, 2024)
This commentary to Clayton Crockett’s Energy and Change: A New Materialist Cosmology details his use of systems concepts as it extends his energy framework to conceive of the ecohuman, a new concept that broadens anthropocentric and humanist traditions’ forms of thinking the human being. A review of Crockett’s book gives way to speculations about what the ecohuman is, and how it might be thought across discourses in posthumanism, new materialism, systems theory, and philosophy.
Keywords: energy; entropy; new materialism; cosmotheogeny; ecohuman